Heat therapy in rheumatic and musculoskeletal diseases – an overview of clinical and molecular effects - Philipp Klemm; Nils Schulz; Priyanka Boettger; Uwe Lange (International Journal of Hyperthermia)
Rheumatic and musculoskeletal diseases (RMDs) usually lead to morphological and functional deficits of various extend, increased morbidity and a considerable loss of quality of life. Modern pharmacological treatment has become effective and can stop disease progression. Nonetheless, disease progression is often only slowed down. Moreover, pharmacological treatment does not improve functionality per se. Therefore, multimodal treatment of rheumatic disorders with physical therapy being a key element is of central importance for best outcomes. In recent years, research into physical medicine shifted from a sole investigation of its clinical effects to a combined investigation of clinical effects and potential changes in the molecular level (e.g., inflammatory cytokines and the cellular autoimmune system), thus offering new explanations of clinical effects of physical therapy. In this review we provide an overview of studies investigating different heat applications in RMDs, their effect on disease activity, pain and their influence on the molecular level.